Implementasi Kebijakan Konversi Desa Menjadi Kelurahan - Wirdayanti, Agnes (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2010)
The research aims to describe the factors that support the successful implementation of amalgamation policy of Depok from a County to a City from 2001 up to 2006. The research used descriptive qualitative approach. The result shows that theimplementation of the amalgamation policy ran well since there was no resistance from the people, County and City apparatuses. The factors that affect the amalgamation policy are: communication, resources, the executor’s attitude and the bureaucracy structure of City apparatuses; they become the main subject in the governance process. Quantitatively the number of City employees are sufficient, however qualitatively it is not adequate. These are problems that challenge the local government of Depok. Therefore we need policies and strategies to improve the quality of the apparatuses in order to best serve our people..